Mechanical Simulation of the Extension and Flexion of the Elbow Joint in Rehabilitation - Iman Vahdat; Mostafa Rostami; Farhad Tabatabai Qomshe; Iraj Abdollahi; Nima Soleymanzadeh-Ardabili (University of Social Welfare and Rehabilitation Sciences, 2013)
Objective: The goal of the present study was to improve the extension and flexion of the elbow joint for rehabilitation purposes, in terms of energy dissipation and of injuries caused by stress imposed on connective tissue by exercise equipments during force transfer , by investigation of viscoelastic property variations during change in speed of motion. Materials & Methods: A sample of five men without any previous neuromuscular impairment of the elbow joint was chosen by the BMI factor. The passive continuous motion test (CPM) was performed by the CYBEX isokinetic system in the extension and flexion movements of the elbow joint of the left hand, at 4 different speeds (15, 45, 75 and120 Deg/s) during 5 consecutive cycles at the range of motion of about 0 to 130 degrees. The experimental data was exported to the MATLAB software for analysis. In order to determine viscoelastic property effects and biomechanical parameters, we used a passive viscoelastic mechanical model constructed by 3 elements for simulation, and also we used the curve fitting method to derive the elastic and viscose coefficients for the model.,. Results: Results of experiments showed that by increasing the speed of motion, the value of work done, hysteresis and elastic coefficient increased and the value of viscose coefficient decreased. Also, it appeared that by increasing the speed of motion, the effect of viscose resistance on the passive torque curves increased. In addition, there was significant correlation between the action of the mechanical model and the action of the concerned limbs, during the movement. Conclusion: It was concluded that in order to improve motion and to reduce imposed risks and injuries to joints and limbs, rehabilitation exercises better be performed at lower speeds and with rehabilitation equipments supported by viscoelastic resistant force.